2019
DOI: 10.1111/andr.12613
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of arsenic exposure and diabetes on male reproductive functions

Abstract: Background: It is known that exposure to either arsenic or hyperglycemia can induce male reproductive damages. However, their combined effects on male reproductive organs are still unclear. Therefore, the present study investigated morphological and functional parameters of the testis, epididymis, and spermatozoa in diabetic rats exposed to arsenate. Materials and methods: Diabetes was induced in male rats by intraperitoneal streptozotocin injection. While a set of healthy and diabetic animals received saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…Notably, testis and epididymis are well known as androgen-dependent organs (Mäkelä et al, 2019). Moreover, in STZ-induced diabetic animals, studies indicated that low testosterone level is a relevant factor acting on the morphometrical alterations observed here, such as reduction in the tubular diameter, the epithelial height, and the number of Sertoli and germ cells that, in the end, influenced the diminished DSP (Kianifard et al, 2012; Korejo et al, 2016; Das et al, 2017; Corrêa et al, 2019; Souza et al, 2019). Altogether, these results confirmed the adverse effects of diabetes on the testis and epididymis of Wistar rats.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Notably, testis and epididymis are well known as androgen-dependent organs (Mäkelä et al, 2019). Moreover, in STZ-induced diabetic animals, studies indicated that low testosterone level is a relevant factor acting on the morphometrical alterations observed here, such as reduction in the tubular diameter, the epithelial height, and the number of Sertoli and germ cells that, in the end, influenced the diminished DSP (Kianifard et al, 2012; Korejo et al, 2016; Das et al, 2017; Corrêa et al, 2019; Souza et al, 2019). Altogether, these results confirmed the adverse effects of diabetes on the testis and epididymis of Wistar rats.…”
Section: Discussionmentioning
confidence: 83%
“…The decreased proportion of Se in the testis may also contribute to this result by altering the activity of glutathione-related enzymes (Rotruck et al, 1973). While it is well characterized that diabetes disturbs the adaptative mechanism of the testis to act against the ROS (Souza et al, 2019), the antioxidant role of green tea is still controversial. Das et al (2017) reported an increase in the activity of SOD and CAT in the testis of hyperglycemic rats treated with green tea, whereas Roychoudhury et al (2017) described the pro-oxidant activity of green tea catechins in reproductive organs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations